FORENSIC PSYCHOLOGICAL ASSESSMENT OF MATERIALS CONTAINING VERBAL AND NONVERBAL COMPONENTS - M. Kroz; N. Ratinova (Теория и практика судебной экспертизы)
The paper looks at some questions pertaining to the examination of “static” information materials. The presence of nonverbal elements in printed text varies widely depending the nature of the text and the channel of information transfer. The nonverbal components of written speech that are subject to forensic scrutiny include font shape and size, various means of graphic and color emphasis, and spatial composition of text on the carrier. Active use of these components visually highlights certain fragments of the text in order to focus the reader's attention on these fragments.